Effect of drainage channel on separation performance of swirl-vane separator. (January 2023) - Kang, Ruiqi; Xiong, Zhenqin; Ouyang, Shuo; Gong, Shengjie
Highlights: Separation efficiency is improved by removing water through drainage channel. Reverse gas flow through drainage channels deteriorates the water separation. Separation efficiency is sensitive to the arrangement of drainage channels. Adding drainage channels reduces the pressure drop. Abstract: Swirl-vane separator in nuclear reactors removes liquid from gas by centrifugal force. Since liquid film is accumulated on the wall, drainage channels are designed to remove liquid film in time and reduce secondary droplet entrainment. Euler-Euler multiphase numerical model and Realizable k-ε turbulence model are developed to investigate the effect of drainage channels. The results indicate separation efficiency is improved by removing water through drainage channels at low inlet gas velocity, while reverse gas flow from down-comer to riser through drainage channels pushes water near wall to the axis of riser, deteriorating separation at high inlet gas velocity. Moreover, the effect of channel area, size, shape and arrangement are analyzed. Separation performance is most sensitive to drainage channel arrangement compared to size and shape. Evenly distributing drainage channels over a wide range of wall benefits separation of water and reduces reverse gas flow.